Analisis K-Means Cluster untuk Identifikasi Kawasan Pengelolaan Sampah di Kabupaten Tapin Provinsi Kalimantan Selatan - Riry Magriaty; Kukuh Murtilaksono; Syaiful Anwar (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2023)
Population growth of Tapin Regency is projected to grow until it reaches more than 200,000 in 2025. In current conditions, the government can only manage a small amount of solid waste in certain urban settlement areas. Limited service coverage of waste management systems causing a serious threat for environmental quality. The research was intended to determine and identify zone for planning and developing the waste management system in a larger scale area to improve waste management services in Tapin Regency. The research methods using PCA (principal component analysis) then K-Means cluster to obtain waste management zone in that area. The results have shown that waste management zones can be classified into 3 types zone. Zone type 1 consisted of 25 villages located in a urban area that has the highest vulnerability of solid waste generation. Zone type 2 consisted of 36 villages and located relatively close to the rural-urban area which has the highest population growth rate. Zone type 3 consisted of 36 villages located very far from the urban area which has the lowest vulnerability of solid waste generation. Zone type 1 and 2 were determined as priority clusters for developing waste management services which have 73.3% coverage of all area. Waste management systems coverage in zone type 3 implemented by the addition of community participation programs.